KELUARGA BERENCANA DAN KEPENDUDUKAN - Abdul Wahab Syakhrani; Rahmadaniyati, Siti Norhalisa, Siti Ramlah, Yurita Safitri (CV. Adiba Aisha Amira, 2024)
Family Planning (KB) is an eflort or eflort to regulate pregnancy, regulate the birth of children, the distance and age at which children are born, protection and assistance according to reproduction to form and create a prosperous family with healthy quality physically and mentally. The aim is to improve the welfare of the mother, reduce the death rate mothers, babies and children, and controlling births while ensuring controlled population growth.